A Behavioral Perspective on Negotiating International Alliance - Rao, Asha; Schmidt, Stuart M. (Journal of International Business Studies, 1998)
This study examines the influence tactics of senior U.S. executives in negotiating international business alliances. The strategy literature on alliances and the behavioral literature on negotiations were incorporated into a behavioral model of alliance negotiations. Constructs identified from transaction cost, power dependence and game theories were integrated and linked to hypotheses describing negotiators' influence tactics in alliance negotiations. In examining eighty-three alliance negotiations, negotiator trust, perception of a partner firm's alternatives, conflict frame, time horizon, and cultural distance were found to affect negotiators' tactics.